2016
DOI: 10.1016/j.porgcoat.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-plasticizer compatibility during coating formulation: A multi-scale investigation

Abstract: During the formulation of solid dosage forms coating, plasticizers are added to the film forming polymer to improve the mechanical properties of the coating shell of the drug product. For the coating formulation to be successful and in order to produce flexible continuous film, the plasticizer should be compatible with the film forming polymer (i.e. high plasticizer-polymer miscibility in solid dispersion) (McGinity and Felton, 2008). This paper proposes and compares different multi-scale methods to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 49 publications
1
36
0
2
Order By: Relevance
“…However, the phthalate esters are easy to migrate from polymer matrix during processing and using with increasing time, which decreases the service life of polymer products, as well as potential toxicity to human body 11 , 12 . Recently, epoxidized vegetable oil 13 , 14 , polymer plasticizer 13 , 15 , polyol ester 16 , 17 and phosphate plasticizer 14 have been reported as alternative plasticizers, which suppresses the migration from PVC products in a certain degree, but epoxidized vegetable oil, polyol ester and phosphate plasticizer will migrate from PVC products with increasing time. The effective strategy to avoid the migration of plasticizers is covalent attachment of the plasticizer onto the PVC backbone 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the phthalate esters are easy to migrate from polymer matrix during processing and using with increasing time, which decreases the service life of polymer products, as well as potential toxicity to human body 11 , 12 . Recently, epoxidized vegetable oil 13 , 14 , polymer plasticizer 13 , 15 , polyol ester 16 , 17 and phosphate plasticizer 14 have been reported as alternative plasticizers, which suppresses the migration from PVC products in a certain degree, but epoxidized vegetable oil, polyol ester and phosphate plasticizer will migrate from PVC products with increasing time. The effective strategy to avoid the migration of plasticizers is covalent attachment of the plasticizer onto the PVC backbone 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the anion of the ionic liquid can affect the Tg of the GAP/ionic liquid plasticizer. These changes could result in the variation of ion movement and anion‐cation Van der Waals force .…”
Section: Resultsmentioning
confidence: 99%
“…In our studies on the effect of the ionic liquid type on the Tg of the GAP, we found that the anion changes of the ionic liquid plasticizer from bromide to dicyanamide led to the reduction of Tg up to 9 °C. The reason for this reduction could be the change in the ion movement and anion‐cation Van der Waals force, because increasing the ions size enhanced the Van der Waals force ,…”
Section: Resultsmentioning
confidence: 99%
“…However, the most important drawback in the application of GAP is its rather low flexibility in a pure state. For more durability and flexibility, plasticizers are often used together with this material . Plasticizers are normally small molecules inserted between the polymeric chains to improve the flexibility and processability features of the propellant mixture.…”
Section: Introductionmentioning
confidence: 99%